KEUNGGULAN KOMPETITIF DAN PENAWARAN EKSPOR TUNA INDONESIA DI PASAR INTERNASIONAL MARKET SHARE CONSTANT ANALYSIS - Suwarno Suwarno; Rina Oktaviani; Hermanto Siregar; Endah Murniningtyas (IPB University, 2012)
The purposes of this study are to analyze sources of tuna export growth in international market. The analysis methode of this study is Constant Market Share Analyis (CMSA). Based on the result study, Indonesia show an increase in tuna commodity export in international market because of an increase export growth in international market. Indonesia has an increase in competitiveness for frozen tuna, for example yellowfin tuna, skypjack tuna, tuna ness, and for prepared-preserved tuna, for example skypjack tuna. The important factors affecting tuna export supply are gross national product and tuna production. Keywords: tuna, Constant Market Share Analyis, competitiveness, export supply.